Peran Model Jaring Laba-laba dalam Pembelajaran Terpadu untuk Meningkatkan Efektivitas Belajar Siswa Sekolah Dasar - Iskandar , Sofyan; Sholihah Rosmana , Primanita; Apriliani , Delia; Azahra, Resa; Andria Sukmawati , Vika (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
There are many learning models in integrated learning. One of the most popular models in primary schools is the spider web model, as it is considered easy to use and suitable for primary school students. The purpose of this article is to ascertain the role of the spider web integrated learning model in improving the learning effectiveness of primary school students. The research method used is the literature study method, which can also be called a literature study. This article describes the role of the spider web model in integrated learning to improve the effectiveness of elementary school students' learning. The spider web model in integrated learning is considered to increase the effectiveness of student learning. This is due to the thematic approach that allows students to search, explore, and analyze information relevant to the theme being studied. This model also emphasizes the role of students as the main subject in the learning process, which is believed to reduce weaknesses in learning skills that usually appear in conventional learning.Â